2022
DOI: 10.1002/gea.21913
|View full text |Cite
|
Sign up to set email alerts
|

Provenance, production, and distribution of basalt and volcanic glass artifacts in Leeward Kohala, Hawaiʻi Island

Abstract: We examined 2947 basalt and volcanic glass artifacts from 38 sites in leeward Kohala. Nondestructive energy‐dispersive X‐ray fluorescence provided initial geochemical characterizations. Wavelength‐dispersive X‐ray fluorescence (WDXRF) and thermal ionization mass spectrometry (TIMS) analyses were completed on samples from ambiguously sourced groups. No more than 13.9% of the probable and definite adze‐related debitage originated in leeward Kohala. Notably absent are lithic materials from the nearby Pololū Adze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Lass (1994) suggested that stoneworkers in the valley acquired loose stone cobbles from the main stream, then detached flakes for adze blanks. Pololū adzes were found at several coastal sites around Hawai‘i Island (Lass, 1994), although were rarely distributed beyond windward Kohala (Mills & Lundblad, 2014; Mills et al., 2022).…”
Section: The Quarries and Sources Of Polynesiamentioning
confidence: 99%
“…Lass (1994) suggested that stoneworkers in the valley acquired loose stone cobbles from the main stream, then detached flakes for adze blanks. Pololū adzes were found at several coastal sites around Hawai‘i Island (Lass, 1994), although were rarely distributed beyond windward Kohala (Mills & Lundblad, 2014; Mills et al., 2022).…”
Section: The Quarries and Sources Of Polynesiamentioning
confidence: 99%
“…In most of these studies the goal was to determine regional provenience or to match artifacts to site‐specific quarries. XRF has been used in some geochemical studies of basalt artifacts in order to identify the regional rock formations, outcrops, or even specific quarries from which they were sourced (e.g., Latham et al, 1992; Linthout et al, 2009; Mills et al, 2022).…”
Section: Introductionmentioning
confidence: 99%